2018
DOI: 10.1021/acs.jproteome.8b00359
|View full text |Cite
|
Sign up to set email alerts
|

Fast Open Modification Spectral Library Searching through Approximate Nearest Neighbor Indexing

Abstract: Open modification searching (OMS) is a powerful search strategy that identifies peptides carrying any type of modification by allowing a modified spectrum to match against its unmodified variant by using a very wide precursor mass window. A drawback of this strategy, however, is that it leads to a large increase in search time. Although performing an open search can be done using existing spectral library search engines by simply setting a wide precursor mass window, none of these tools have been optimized for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 69 publications
0
90
0
Order By: Relevance
“…Second, because the sensitivity of multidimensional indexing techniques decreases as the dimensionality increases, due to the curse of dimensionality [18], shorter vectors are preferred. Previously, we empirically found that mass bins of 1 Da represented a good trade-off between fragment mass resolution and vector dimensionality [8].…”
Section: Feature Hashing To Vectorize High-resolution Mass Spectramentioning
confidence: 98%
See 3 more Smart Citations
“…Second, because the sensitivity of multidimensional indexing techniques decreases as the dimensionality increases, due to the curse of dimensionality [18], shorter vectors are preferred. Previously, we empirically found that mass bins of 1 Da represented a good trade-off between fragment mass resolution and vector dimensionality [8].…”
Section: Feature Hashing To Vectorize High-resolution Mass Spectramentioning
confidence: 98%
“…To build an ANN index to efficiently select candidates from the spectral library, spectra are vec-torized to represent them as points in a multidimensional space. In previous work [8], we converted spectra to sparse vectors by dividing the mass range into equally spaced bins and assigning each peak's intensity to the corresponding bin. When choosing the mass bin width two conflicting factors must be considered.…”
Section: Feature Hashing To Vectorize High-resolution Mass Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, if the exact combination of peptide sequence, amino acid modifications, and charge state is not present in the search space, then the spectrum cannot be correctly identified. Several groups have demonstrated the ability to open the search space to consider unpredicted modifications [5][6][7][8][9] , but these strategies generally lead to an overall decrease in identifications at a given FDR threshold, so are not widely adopted in bottom-up proteomics.…”
Section: Introductionmentioning
confidence: 99%